Hypocrisy Unmasked : Dissociation, Shame, and the Ethics of Inauthenticity. - Naso, Ronald C. (Rowman & Littlefield Pub. Group, 2010)
Hypocrisy Unmasked explores the motives, meanings, and mechanisms of hypocrisy, challenging two principal psychoanalytic assumptions: First, that hypocrisy expresses deviant, uncontrollable impulses or follows exclusively from superego weakness; andsecond, that it can be understood solely in terms of intrapsychic factors without reference to the influences of the field. Ronald C. Naso argues that each of these assumptions devolve into criticisms rather than explanations and demonstrates that hypocrisy represents a compromise among intrapsychic, interpersonal, situational, and cultural/linguist.